Brexit and the limits of financial power in the UK - Scott James; Lucia Quaglia (University of Oxford, Global Economic Governance Programme (GEG), 2017)
Brexit poses a profound challenge to the economic fortunes of the City of London. Recognising this, the UK financial sector campaigned for a Remain vote in the June 2016 EU referendum, and has subsequently lobbied for a "soft" Brexit policy to guarantee continued access to the EU's single market. Despite this, the newly-formed government led by Theresa May has pursued a "hard" Brexit policy which will see the UK withdraw from both the single market and customs union. This is puzzling because it is potentially highly damaging for the UK national business model, characterised by a large, internationalised and competitive financial sector that is dependent on exports to the EU. How can we explain the City's apparent failure to influence the UK's Brexit policy? We argue that while the UK financial sector continues to wield formidable "latent" structural power, its capacity to translate this into instrumental forms of influence within government has been constrained by three factors. First, the high political salience of Brexit has reduced the effectiveness of City lobbying, which traditionally operates through closed networks of influence. Second, institutional reform within government has challenged the traditional City-Treasury-Bank of England "nexus", thereby weakening the representation of the City's interests within government. Third, the City itself is deeply divided on this Brexit issue, constraining the industry's capacity to organise collectively to influence policy makers.
Keywords: 330